Space-based long term condition monitoring of cold region pavement with PS-InSAR - Yusheng Jiang; Xiong Yu (Journal of Infrastructure Preservation and Resilience)
Abstract The durability of cold-climate pavement is affected by ground frost heave and thaw settlement. Field monitoring of pavement elevation changes remain challenging and expansive. This study demonstrates space-based Interferometric Synthetic Aperture Radar (InSAR) technology as a potential way to monitor seasonal pavement elevation change in cold region. Traditional InSAR applications, which were designed for geoscience scales, do not achieve the needed sensitivity or spatial resolution for pavement engineering applications. The testbed used is a cold-region airport located in Qinghai Province, China. The site contains heterogeneous ground conditions in an area of 4km $$×$$ × 6km. Analyses were conducted using 132 ascending and 149 descending C-band InSAR images from the Sentinel-1 satellite. InSAR algorithm based on Persistent scatterers (PS-InSAR) were implemented for data analyses. Time series displacement across five distinct persistent scatterers (PSs) groups at different locations were obtained. From these, three main seasonal vertical ground deformation patterns were identified, each reflecting the diverse subsurface soil characteristics across the sites. The ground elevation changes were decomposed into baseline trend and seasonal changes. The results of seasonal ground deformations allowed to differentiate the ground soils as frost-susceptible and non-frost-susceptible, an important information for geotechnical site investigation. This helps identify areas of pavement subjected to frost heave and thaw weakening. The study demonstrates that potential of space-based InSAR technology to achieve spatial resolution and sensitivity for monitoring the performance of cold region pavement. The results allow to identify areas of pavement vulnerable to cold region climate and climate change.